Evaluation of anthelmintic activity of rhizomes of Hedychium spicatum Buch.Ham. - Sravani T.; Padmaa M Paarakh (International Journal of Research in Pharmaceutical Sciences, 2011)
Hedychium spicatum Buch. Ham. (Zingiberaceae), commonly known as spiked ginger lily, is found in the entire Himalayan region. Traditionally, the rhizomes are used in the treatment of respiratory disorders, fevers, tranquilizer, hypotensive, antispasmodic, CNS depresant, analgestic, anti-inflammatory, antimicrobial, antioxidant, antifungal, pediculicidal and cytotoxic activities. The present study is an attempt to explore the anthelmintic activity of rhizomes of Hedychium spicatum against adult Indian earthworms, Pheretima posthuma. The time taken for each worm for paralysis and death was determined. The results were compared with that of standard i.e., piperazine citrate. Methanol extract of Hedychium spicatum produced dose dependent anthelmintic activity whereas aqueous extract was not all effective. Methanol extract showed better anthelmintic activity when compared with the standard drug piperazine citrate.